Linear Optimal Designs and Optimal Contingency Plans - Lee, Y. R.; Shi, Y.; Yu, P. L. (Management Science, 1990)
In optimal design problems we try to select a subset from the opportunity set for commitment for a period of time. As the external parameters can vary with time, optimal contingency plans must be constructed to cope with the external conditions. We describe the formulation and methods for locating potentially good designs and their corresponding optimal contingency plans using a multiple-criteria and multiple-constraint level (MC 2 ) simplex method to solve the optimal design problems which have been shown to become amenable to the techniques of decision making under uncertainty.